Privatizacija gozdarske svetovalne dejavnosti kot poslovna priložnost za diplomante gozdarstva - Jevšenak, Jernej (Gozdarski vestnik, 2013)
Reduced level of employability of forest graduates in Slovenia is exposed. In this contribution a political solution concerning payable forestry consulting business is presented. That also means a slight change in the organization of forestry in Slovenia. Article deals with some other employment markets for forestry graduates in Europe and highlights the niche of forestry consultants. Proposed solution measure is analyzed in terms of feasibility and efficiency.
Keywords: forestry; gozdarstvo; privatizacija; brezposelnost; unemployment; svetovanje; gozdarski delavci